Verso una letteratura transculturale - Taddeo, Raffaele (TransCulturale, 2022)
This essay focuses on transculturality. It starts by discussing the prefix ‘trans’ and engages with the scholarly debate around meanings that may be attributed to it. The essay then evaluates the possibility to apply transculturality to the area of literary studies, beyond medical and pedagogical disciplines. Considering that there is a tendency to use the concept of transculturality to refer to writers coming from other cultures or languages, this essay argues that a transcultural element exists in any authentic literary writer. This feature may exist provided that such writer goes through a more personal decolonisation phase, is inclined to considering the other, and knows how to recognise elements that are proper to human beings, such as their needs, purpose, and universal feelings.